2004
DOI: 10.1086/380973
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic Factors for Severe Acute Respiratory Syndrome: A Clinical Analysis of 165 Cases

Abstract: This study analyzes single factors that affect the prognosis of severe acute respiratory syndrome (SARS) and establishes a prognosis model by multivariate analysis. We retrospectively analyzed the clinical features of SARS in 165 clinically confirmed severe cases. Both age and existence of other diseases before SARS were significantly correlated with prognosis (r=0.506 and r=0.457, respectively; P<.001). During the acute phase of SARS, lactate dehydrogenase level, degree of hypoxemia, respiratory rate, alpha -… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
51
1
1

Year Published

2004
2004
2021
2021

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 54 publications
(57 citation statements)
references
References 6 publications
4
51
1
1
Order By: Relevance
“…In adults, the risk factors for severe illness are advanced age, high initial absolute neutrophil counts, low platelet counts, high initial or peak lactate dehydrogenase levels and positive RT-PCR results for NPA specimens. 6,[106][107][108][109] Only one paediatric series has identified risk factors for severe illness in terms of requirements for oxygen and intensive care. These include a sore throat, a high neutrophil count at presentation, and peak neutrophilia.…”
Section: Prognosismentioning
confidence: 99%
“…In adults, the risk factors for severe illness are advanced age, high initial absolute neutrophil counts, low platelet counts, high initial or peak lactate dehydrogenase levels and positive RT-PCR results for NPA specimens. 6,[106][107][108][109] Only one paediatric series has identified risk factors for severe illness in terms of requirements for oxygen and intensive care. These include a sore throat, a high neutrophil count at presentation, and peak neutrophilia.…”
Section: Prognosismentioning
confidence: 99%
“…In addition, we screened the expression of SARS-CoV receptor angiotensin-converting enzyme 2 (ACE2) on both peripheral DC and lymphocyte populations, and examined associations between DC number and specific antibody generation. [20]. Among these patients, thirtyone are males and forty-three are females.…”
Section: Introductionmentioning
confidence: 98%
“…It has been reported that for patients with SARS, old age and comorbities are more likely to be associated with a high mortality (17-20). In patients with SARS, the mortality rate for patients over the age of 50 years was 13 times higher than for patients younger than 50 years (17).…”
Section: Discussionmentioning
confidence: 99%
“…Actually, 55-61% of the patients with SARS had thrombocytopenia initially, and 35-49% of victims had reactive thrombocytosis in the late stage (17). In our series, the lowest (mean 91.00/mm 3 ± 23.06) and highest (mean 487.13/mm 3 ± 60.52) platelet count was observed at the mean on day 16 and day 23 after the onset of fever, respectively.…”
Section: Discussionmentioning
confidence: 99%